Oil Revenue and Non-Oil Revenue Impact on Economic Development - Olasupo, Sunday; Owolabi , Babatunde; Owolabi, Oluwasikemi; Akinbode , James; Afolabi , Oladiran; Otekunrin, Adegbola; Osueke, Chikamso; Omojola, Sunday; Doorasamy, Mishelle (International Journal of Energy Economics and Policy, 2025)
The lingering controversy on the right mix of national revenue generation in a quest for economic development is more pertinent for resource-rich and development-deficient countries, such as Nigeria. Even though Nigeria earns substantial revenue from oil exports, it still performs poorly in basic human development indicators such as health, education, and income. This paper examines the effects of oil revenue (OILREV) and non-oil revenue (NONOILREV) on the economy in Nigeria, measured using the Human Development Index (HDI) as a measure of economic advancement. The study adopted an ex-post facto research design in which secondary data were obtained from World Bank databases and the Central Bank of Nigeria (CBN) from 2014 to 2024. Independent variables used were Oil Revenue (OILREV) and Non-Oil Revenue (NONOILREV), with HDI as the dependent variable. The study applied a panel least squares estimation technique using unbalanced panel data with 86 observations across sections. The empirical findings show that oil and non-oil revenues both have statistically significant positive effects on HDI. Specifically, an increment in oil revenue by one unit boosts HDI by 0.000604 units (p = 0.0000), whereas an increase in non-oil revenue by one unit boosts HDI by 0.000447 units (p = 0.0000). These findings show that oil revenue has a slightly higher effect on human development compared to non-oil revenue. However, the significance of both highlights the significance of diversified sources of revenue. The study concludes that Nigeria's economic growth can significantly be enhanced by the strategic management of both oil and non-oil sources of revenue.